Econometric Analysis of the Deficit Financing Options-Growth Inclusiveness Nexus in India and Nigeria (2020)
The crux of the study was to ascertain whether (and to what extent) the different defi cit financing options impacted inclusive growth in India and Nigeria. The paper con ducted an empirical analysis using data covering the period from 1989 to 2018 using the ARDL model. Some interesting results were obtained. First, foreign aid positively impacted inclusive growth in both short and long run for Nigeria. Contrarily, the results for India presented an inverse relationship between aid and inclusive growth with no statistical significance in the short and long run. Second, the impact of borrowing on inclusive growth was significant and negative for short run and long run in India. In the Nigerian case, the findings highlighted a positive and significant effect of borrowing on inclusive growth for both time horizons. Third, on the issue of human capital investments, the government expenditure on education effect on growth inclusiveness was found to be positive and negative in the short and long run, respectively, for India. On the other hand, government expenditure on health was negative in the short run and positive in the long run in Nigeria. Thus, there are a number of relatable policy recommendations viz: (i) Nigeria needs to utilize its borrowing options more effectively by undertaking relevant infrastructural and human capital investments; (ii) Instead of reliance on foreign aid for growth, Nigeria could join the liquidity race by attracting more diaspora remittances like its comparator India; (iii) The government of India should devote even more resources to capital expenditure to drive long-term investments and ensure that a greater number of citizens benefit from the process.